0950 Protein value of eight triticale genotypes for pigs based on standardized ileal amino acid digestibility. (1st October 2016) - Strang, E. J. P.; Eklund, M.; Rosenfelder, P.; Htoo, J. K.; Mosenthin, R.
Abstract: The study was conducted to determine the chemical composition, physical characteristics and standardized ileal digestibility (SID) of CP and AA of 8 currently available genotypes of triticale fed to growing pigs. The experiment was conducted with 8 barrows (initial BW of 30 ± 2 kg) that were fitted with a simple T-cannula at the distal ileum. The pigs were randomly allotted to an 8 × 8 Latin square design. Diets were based on 1 of the 8 triticale genotypes each, with triticale as the sole source of CP and AA. An N-free diet was fed to determine basal ileal endogenous losses of CP and AA. Diets were supplemented with titanium dioxide as an indigestible marker, and fed at a daily intake level of 4% of pigs' average BW corresponding to about 3 times the pigs' energy requirement for maintenance (106 kcal of ME/kg of BW 0.75 ). Each experimental period consisted of 5 d for adaptation to the diets and 2 d for ileal digesta collection. Ileal digesta samples were collected consecutively for a total of 24 h. Data were analyzed by the Mixed Procedure of SAS with genotype and pig as fixed effects; period and period × pig were considered as random effects. The CP and non-starch polysaccharide (NSP) contents (as-fed basis) of the 8 triticale genotypes ranged from 10.5 to 11.8% and 8.5 to 10.0%, respectively. The greatest contents of NDF, ADF and ADL in the 8 genotypes amounted to 14.9, 2.9 and 0.6% (as-fed basis), respectively. Among the 8 genotypes, SID of CP, Lys, Met, Thr and Trp ranged from 81 to 85, 72 to 77, 84 to 87, 73 to 77 and 79 to 83%, respectively. The SID of CP and AA did not differ among the 8 triticale genotypes, except for SID of Arg, Glu and Gly ( P ≤ 0.05). The SID of CP and AA was not affected by NSP or NDF content due to the small variations of these fiber fractions among genotypes. Compared to SID values for triticale in current feed tables, the SID of CP, Lys, Met and Trp in the present 8 triticale genotypes was up to 4, 4, 4, and 1%-units lower, respectively, and up to 5%-units higher for Thr. These differences in SID of AA need to be accounted for in diet formulation for pigs when new genotypes of triticale are used.